Photoluminescence and X-ray excited scintillating properties of Tb3+-doped borosilicate aluminate glass scintillators. Issue 12 (15th June 2022) - Huang, WenJun; Wen, ZhuoXing; Li, LianJie; Ashraf, Ghulam Abbas; Chen, LiPing; Lei, Lei; Guo, Hai; Li, XiaoMan
Abstract: lthough single crystal scintillators have excellent performance, they have some drawbacks such as high cost, complicated elaboration method and difficulty of growth on large-scale. Glass scintillators are widely investigated to replace single crystal scintillators because of their simple fabrication method and low cost. In this paper, a series of transparent borosilicate aluminate glass scintillators doped with Tb 3+ were successfully prepared by traditional melt-quenching method. The structural, luminescent, and X-ray excited scintillating properties were investigated. These glass samples show high stability and high transparency, and present good luminescent and scintillating properties. Sample with Tb 3+ doping concentration of 10% has the best scintillating performance. The integrated intensity of X-ray excited luminescence is 66.6% of that of commercial Bi4 Ge3 O12 single crystal scintillator, and the quantum efficiency (under 378 nm excitation) is 70.3%. Our findings suggest that Tb 3+ -doped borosilicate aluminate glasses with high light yield might be used as potential scintillators.